Prediction Analysis on the Transport Distance of Supply Air in Warm Air Heating Room with Impinging Jet Ventilation Systems - 陈新秋 钟珂 卢思亮 亢燕铭 (东华大学学报（英文版）, 2015)
To overcome the disadvantages of displacement ventilation（ DV） and traditional mixing ventilation（ MV） system,a new ventilation system known as impinging jet ventilation system（ IJVS）has been developing. The warm air can be supplied with impinging jet ventilation（ IJV）, while the DV is only used for cooling.However,the flow and temperature field of IJV under heating scenario has had few references. The paper is mainly focused on computational fluid dynamics（ CFD） and developing an adequate correlation between the distance L that warm air can reach and different parameters in the warm IJVS by using response surface methodology（ RSM）. The results indicate that L decreases as the supply velocity υ decreases but increases as the supply temperature difference ΔT or the discharge height h decreases. In the variable air volume（ VAV） system, it is necessary to determine supply parameters both under the maximum-heat-load condition and the small-heat-load condition. Unlike the VAV system,the constant air volume（ CAV） system has no need to study the small-heat-load condition. Draught discomfort near the nozzle becomes the issue of concern in IJVS, thus the suitable discharge height is of great importance in design and can be calculated based on the predictive model.